Letter (copy) : Spanish Relief Fund - Tewson, Vincent
029-0150-001 HVT/EK/979. Secretary's. 28th May, 1937. Mr. Cecil J. Beer, Viceconsulado de Espana, Newport, MON. Dear Mr. Beer, SPANISH RELIEF FUND. I have your letter of the 21 at instant and have deferred replying in the hope of making contact with the Spanish Women's Committee to which you refer. I have not yet been able to do this, but I am trying to arrange for a representative to come to see me on Monday next, when we will examine the position. I may say that we have received a letter from Sra. Carmen de Cossio in terms similar to your own. Yours sincerely, Assistant Secretary. 292/946/29/150